(3QSGdI aj GdTjNhNI hTQhW GdeQjOs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GHf GdYQHi GdMeO ddg GdPj gOGfG dgPG heG cfG dfgJOi dhdG Cf gOGfG Gddg s
(3BNQgG (B:s
(3hCYfj gPG HGdMb bj SjQI GdefGRd eG jfRd ef Gddg JYGdi Ydjge ef GddWGFa gPG BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3GdTjNhNI Cj GdTjNs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3eLGejY Mdje (B1/33580) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs